Effects of Capital, Usage of Accounting Information, Financial Statements, and Characteristics Entrepreneurship on Financial Capability and Business Performance of MSMEs - Henky Hendrawan; Asri Ady Bakri; Acep Fatchuroji; Fauzi; Rustam Effendi (Eastasouth Institute, 2023)
This study aims to investigate the influence of capital, use of accounting information, financial reporting, and entrepreneurship on the financial capability and business performance of micro, small, and medium-sized enterprises (MSMEs) in Bogor, Indonesia. A cross-sectional survey was conducted, and data were collected from 200 MSMEs using a structured questionnaire. Smart-PLS was used to analyze the data and test the research hypotheses. The findings indicate that capital, use of accounting information, financial reporting, and entrepreneurship have a significant positive influence on the financial capability and business performance of MSMEs in Bogor These results suggest that MSMEs should prioritize obtaining sufficient capital, ensuring access to reliable accounting information and financial reporting, and developing entrepreneurial skills to improve their financial capability and business performance. The practical implications of this study suggest that MSMEs should focus on obtaining sufficient capital to invest in their businesses, ensuring access to reliable accounting information and financial reporting to make wise financial decisions, and developing entrepreneurial skills to identify and capitalize on opportunities in the market. This study has several limitations, including the use of self-reported data and a cross-sectional design, which limits the generalizability of the findings. Future research could address the limitations of this study by conducting longitudinal research using objective measures of financial capability and business performance. Additionally, similar studies could be conducted in other geographical locations to test the generalizability of the findings. Overall, this study provides important insights into the factors that contribute to the success of MSMEs and has practical implications for MSMEs in Bogor, Indonesia.